2022
DOI: 10.3389/fnut.2022.908355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intramuscular fat on meat quality and its regulation mechanism in Tan sheep

Abstract: Intramuscular fat (IMF) contributes importantly to various aspects of meat quality, and genetic regulation is an effective pathway to improve IMF deposition in sheep. In this study, we systematically explored the effect of IMF content on meat quality in Tan sheep and investigated the regulatory mechanism of flavor precursors metabolism and IMF deposition. The results revealed that IMF significantly affected meat color, total muscle fiber numbers, and muscle fiber types in Tan sheep. Widely-targeted metabolomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 56 publications
4
23
0
Order By: Relevance
“…There was a much larger variation within breeds, in IMF content. Variation in IMF within breeds affects meat quality characteristics such as shear force, texture, and color coordinates ( 1 , 22 ). Consumer sensory evaluation shows that lamb overall palatability increases markedly at around 3% IMF and peaks at 4% IMF ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a much larger variation within breeds, in IMF content. Variation in IMF within breeds affects meat quality characteristics such as shear force, texture, and color coordinates ( 1 , 22 ). Consumer sensory evaluation shows that lamb overall palatability increases markedly at around 3% IMF and peaks at 4% IMF ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in pork from high-fat Duroc pigs that the IMF content linearly related to the Warner-Bratzler shear force ( 29 ). Zhang et al concluded that the IMF content positively correlated with color coordinates, namely, lightness, redness, yellowness, and the IMF variation within Tan sheep was ascribed to the difference in meat color ( 22 ). Inconsistent with these findings, the IMF content did not correlate with shear force or color coordinates in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IMF contributes a key factor to meat quality [ 38 ]. This process is regulated by lipid-forming transcription factors such as the C/EBPα and PPARγ .…”
Section: Discussionmentioning
confidence: 99%
“…Crude fat content in cauda epididymis of one hundred twenty rams was measured with the Soxhlet method as previously described [ 14 ]. Fatty acid content in the freeze-dried epididymal tissue (0.2 g) were extracted using chloroform/methanol extraction methods referred to O’Fallon et al [ 15 ].…”
Section: Methodsmentioning
confidence: 99%